The use of Deauville 5-point score could reduce the risk of false-positive fluorodeoxyglucose-positron emission tomography in the posttherapy evaluation of patients with primary bone lymphomas - Rigacci, Luigi; Kovalchuk, Sofia; Berti, Valentina; Puccini, Benedetta; Mannelli, Lara; Benelli, Gemma; Dini, Catia; Pupi, Alberto; Bosi, Alberto (World Journal of Nuclear Medicine, 2018)
Primary bone lymphoma (PBL) is a rare disease. Little is reported about response evaluation procedures in these patients. Our aim was to evaluate response to therapy according to fluorodeoxyglucose-positron emission tomography (FDG-PET) results, and in particular to test the Deauville 5-point scale as compared to the visual evaluation of FDG-PET scans in PBL. In this single-center study, we diagnosed 31 consecutive patients with PBL, of which 24 were evaluated with end-of-treatment FDG-PET. Patients' ages ranged from 19 to 82 years. Six patients were treated with chemotherapy, 24 with chemotherapy and radiotherapy, and one patient with radiotherapy alone. Six patients were affected by a pathological fracture. Four patients died within the range of 3 to 36 months after diagnosis. The average follow-up of the remaining patients was 70 (24–173) months. Overall survival was 87% at 5 years. The only positive prognostic factor was complete remission after chemotherapy. According to visual criteria, end-of-treatment FDG-PET was evaluated in 24 patients and it was positive in 11 (46%) and negative in 13 patients. We organized a retrospective central-blinded revision of end-of-therapy FDG-PET scans using the 5-point Deauville Score (DS). We reviewed 17 out of 24 patients and obtained the following results: at the end of therapy, 12 patients with DS score 2, three patients with DS score 3, one patient with DS score 4, and none with DS score 5. Considering that all the 24 patients achieved complete remission after treatment, visual interpretation produced 11/24 false-positive results, and DS interpretation produced 1/17 false-positive results, thus significantly reducing the number of false positives. In PBL, the final evaluation at the end of therapy with FDG-PET should be evaluated using Deauville 5-point scale in order to significantly reduce the risk of false-positive scans.
Keywords: Bone lymphomas; Deauville criteria; false positive